Analisis debit aliran sungai DAS Bila, Sulawesi Selatan - Ikrima Staddal; Oteng Haridjaja; Yayat Hidayat (JURNAL SUMBER DAYA AIR, 2016)
The streamflow is an important component in the management of a watershed. Streamflow data in the form of maximum flow and minimum flow and average discharge can be used for sustainable watershed planning. Bila watershed is a priority watershed in South Sulawesi. Tempe Lake is located at the downstream of Bila watershed, in rainy season Tempe Lake is flooding, and will inundate rice fields, residential and other social infrastructures. In addition of flooding problem, sedimentation factor in Tempe Lake becomes a priority that must be saved.The amount of people needs for agriculture land and settlements resulting in the conversion of catchment area, and this has led to an imbalance hydrology in Bila watershed. This study aimed to observe the effect of landuse changes on streamflow. Streamflow analysis of is done by looking at the value of the maximum and minimum discharge over a period of 10 years and runoff coefficient. The results showed that landuse changes trend has effecting maximum and minimum discharge trends and runoff coefficient. Conversion of primary forests to secondary forests of 8.6% has been changing river conditions from good to bad. River conditions become worse has followed by increased river flow coefficient of 21.9% from 0.56 becomes 0.72, which means that 72% of precipitation in Bila watershed is runoff.